Long-term variability and trends in the Agulhas Leakage and its impacts on the global overturning - H. Großelindemann; H. Großelindemann; F. S. Castruccio; G. Danabasoglu; A. Biastoch; A. Biastoch (Ocean Science)
Agulhas Leakage transports relatively warm and salty Indian Ocean waters into the Atlantic Ocean and as such is an important component of the global ocean circulation. These waters are part of the upper limb of the Atlantic meridional overturning circulation (AMOC), and Agulhas Leakage variability has been linked to AMOC variability. Agulhas Leakage is expected to increase under a warming climate due to a southward shift in the Southern Hemisphere westerlies, which could further influence the AMOC dynamics. This study uses a set of high-resolution preindustrial control, historical and transient simulations with the Community Earth System Model (CESM) with a nominal horizontal resolution of 0.1° for the ocean and sea ice and 0.25° for the atmosphere and land. At these resolutions, the model represents the necessary scales to investigate Agulhas Leakage transport variability and its relation to the AMOC. The simulated Agulhas Leakage transport of 19.7 ± 3 Sv lies well within the observed range of 21.3 ± 4.7 Sv. A positive correlation between the Agulhas Current and the Agulhas Leakage is shown, meaning that an increase of the Agulhas Current transport leads to an increase in Agulhas Leakage. The Agulhas Leakage impacts the strength of the AMOC through Rossby wave dynamics that alter the cross-basin geostrophic balance with a time lag of 2–3 years. Furthermore, the salt transport associated with the Agulhas Leakage influences AMOC dynamics through the salt–advection feedback by reducing the AMOC's freshwater transport at 34° S. The Agulhas Leakage transport indeed increases under a warming climate due to strengthened and southward-shifting winds. In contrast, the Agulhas Current transport decreases due to a decrease in the Indonesian Throughflow and the strength of the wind-driven subtropical gyre. The increase in the Agulhas Leakage is accompanied by a higher salt transport into the Atlantic Ocean, which could play a role in the stability of the AMOC via the salt–advection feedback.